Psychosocial Factors Associated with Depression among Elderly with Chronic Disease - Aulia Pradana Satya Kiran; Rafli Bagas Nugroho; Ahmad Qolbiy (Journal of Medical Practice and Research, 2026)
Depression represents a significant mental health concern among elderly individuals living with chronic diseases, particularly in community healthcare settings where long-term illness management may generate psychological stress. This study aimed to examine the association between psychosocial factors and depression among older adults with chronic diseases. A quantitative analytic study with a cross-sectional design was conducted among 52 elderly individuals diagnosed with hypertension or type 2 diabetes mellitus in the working area of Patuk II Primary Health Care, Gunungkidul Regency, Indonesia. Data were collected using standardized instruments including the Brief COPE Inventory, the Family Support Scale, and the Patient Health Questionnaire-9 (PHQ-9). Descriptive analysis indicated that most participants demonstrated high coping mechanisms and moderate to high levels of family support, while depressive symptoms were present in a smaller proportion of respondents. Spearman rank correlation analysis revealed significant negative associations between coping mechanisms and depression (r = −0.523; p < 0.001) as well as between family support and depression (r = −0.499; p < 0.001). These findings highlight the importance of strengthening psychosocial resources in order to reduce depression risk and promote psychological well-being among elderly individuals with chronic diseases.